Syntrichia laevipila Brid.: A new record species of bryophytes from Zhejiang Province - Hong Chuntao; Miao Lihua; Ji Mengcheng (浙江大学学报. 农业与生命科学版)
Based on specimen examination adopting classical classification method, Syntrichia laevipila Brid. was found and reported for the first time in Zhejiang Province. It distributed both in Xixi Wetland National Park of Hangzhou City and Pingyang County of Wenzhou. The characteristics of distribution and habitat were discussed.In the present paper S. laevipila. was accepted as a species of the genus Syntrichia Brid. rather than the genus Tortula Hedw. of family Pottiaceae. Syntrichia laevipila Brid. was morphologically close to S. sinensis (C. Müll.) Ochyra, a widely-distributed species in Zhejiang Province. Both species were similar in their leaf shape, leaf cell shape and papillosity. However, from S. sinensis (C. Müll.) Ochyra, S. laevipila Brid. could be especially identified by its small size (2-3 mm), colorless spindly leaf apex and 1-2 circle left-handed dentiums.The discovery of the new record of S. laevipila Brid. enriched the bryophyte flora of Zhejiang Province, and also provided fundamental materials to further study geographical distribution of genus Syntrichia Brid. in China.